LESSONS LEARNED FROM COVID-19: HOW DATA VISUALIZATION HAS CHANGED PUBLIC HEALTH COMMUNICATION AND SURVEILLANCE - Maier, Peter (My University, 2022)
This report summarizes the virtual and field experiences captured during my tenure as an intern and employee for the Clay County Public Health Center (CCPHC) during the COVID-19 pandemic. Over the course of three months, I learned various data analytical and epidemiological skills while working under several departments within CCPHC. Dr. Kim Trang served as my site preceptor and provided me tasks during our daily check-ins. The overarching purpose of this integrated learning experience (ILE) is to reflect what working in a local public health agency looks like, along with the policies and principles that are required to run this agency from each level of service. The ILE required a hybrid approach as it took place during some of the worst months of the COVID-19 pandemic. Three days per week were spent in office, while the other two were virtual days from home. The continued frequency and intensity of COVID-19 cases throughout Clay County led to the creation of numerous tasks. The most important task at the beginning of the ILE was carrying out disease case investigation. Disease case investigation required querying a central database that houses all laboratory data with potential positive COVID-19 cases. I assisted in updating this database daily. Investigators noted this information and then placed a phone call to each prospective case to collect further health information. Health information included anything ranging from demographics to length-of-hospital-stay to close contacts and symptomology. As case information was collected, it was entered into a separate tracking system. This system sent out automated text messages to positive patients who could report their daily symptoms into. I extracted this information and processed it in my role as the disease case investigator and data analyst. As COVID-19 cases continued to build up, additional resources and focus were placed on ensuring that all cases were contacted and had adequate support. As more data was collected, we needed a better way to translate this information into an understandable format for public use. Due to my long-standing interest in using graphical methods to portray public health data, I enthusiastically embraced several new responsibilities that focused on data visualization and public health messaging. I created a weekly COVID-19 dashboard that reflected real-time case counts, hospitalizations, and deaths in the community. Additional features included a historical perspective of this information and detailed demographic and geolocation data. These metrics aided the Clay County Health Department’s mission to reduce the spread of COVID-19. The secondary purpose was to combat the spread of misinformation. As dangerous as the COVID-19 pandemic has been, the rampant misinformation has been equally dangerous; therefore, the implementation of a data dashboard remedied the notion that COVID-19 impacted only the elderly and immunocompromised. Finally, I spent time with Clay County’s environmental health team where I assisted with data analytics regarding foodborne illness. We created an annual review of foodborne illness, including outbreak locations and changes over the last five years. This experience allowed me to visit restaurants, hotels, and nursing homes to evaluate their kitchens and serving areas. This provided me an opportunity to experience field epidemiology by assessing a physical location and talking with people who came down with an illness. Additionally, this opportunity provided me with knowledge on standards of care and the policies that exist to protect community health from foodborne pathogens. I am grateful for my time at CCPHC and the mentorship that was provided. Dr. Kastner, as a mentor and supporter of my endeavors, helped me approach this experience in a reflective and thoughtful manner. Coursework completed from Kansas State University and the University of Kansas Medical Center enriched my learning throughout the ILE. Dr. Kim Trang taught me analytical skills that will greatly benefit my future career. I now have a deeper understanding of what public health looks like at the local level and how data visualization can be harnessed to improve health outcomes.
Keywords: Data visualization; Data Analytics; Epidemiology; Health Education; Health Communication